New Phosphorus-Doped Perovskite Oxide as an Oxygen Reduction Reaction Electrocatalyst in an Alkaline Solution - Shen, Y.; Zhu, Y.; Sunarso, J.; Guan, D.; Liu, B.; Liu, H.; Zhou, W.; Shao, Zongping (Wiley - V C H Verlag GmbH & Co. KGaA, 2018)
Because of their structural and compositional flexibility, perovskite oxides represent an attractive alternative electrocatalyst class to precious metals for the oxygen reduction reaction (ORR); an important reaction in fuel cells and metal–air batteries. Partial replacement of the original metal cation with another cation, namely, doping, can be used to tailor the ORR activity of perovskite, for which a metal has been exclusively used as the dopant component in the past. Herein, phosphorus is proposed as a non‐metal dopant for the cation site to develop a new perovskite family with the formula of La0.8Sr0.2Mn1−xPxO3−δ (x=0, 0.02, 0.05, and 0.1; denoted as LSM, LSMP0.02, LSMP0.05, and LSMP0.1, respectively). Powder XRD patterns reveal that the solubility of phosphorus in the perovskite structure is around 0.05. Rotating ring‐disk electrode experiments in the form of linear‐sweep voltammetry scans demonstrated the best ORR performance for LSMP0.05, and also revealed close to a four‐electron ORR pathway for all four compositions. A chronoamperometric test (9000 s) and 500 cycle accelerated durability test demonstrated higher durability for LSMP0.05 relative to that of LSM and the commercial 20 wt % Pt/C catalyst. The higher ORR activity for LSMP0.05 is attributed to the optimised average valence of Mn, as evidenced by combined X‐ray photoelectron spectroscopy and soft X‐ray absorption spectroscopy data. Doping phosphorus into perovskites is an effective way to develop high‐performance electrocatalysts for ORR.